Dampak Pertumbuhan Ekonomi China Terhadap Perekonomian Indonesia - Aulia Keiko Hubbansyah; Wurdaningsih (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2019)
This study aims to analyze the impact of China’s economic growth on the Indonesian economy. In this analysis, the study adapted SVAR with block exogeneity consisting of blocks global variable (China’s economic growth and non-fuel global commodity prices growth) and domestic variable blocks (economic growth, inflation, real interest rates and Indonesia’s exchange rates). Using the data over the period from 1993q1-2017q2, this study found that the shock if China’s economic growth had a major impact on non-fuel global commodity price movements. Additionally, it is also acknowledged that China’s economic growth shock of 1.9 percent causes the Indonesian economy to grow by 0.85 percent. This was due to the appreciation of Rupiah exchange rate againt US Dollar by 1.6 percent, make inflation under control, while inflation in term of rising price index was insignficant